Identifying Ways to Fix Outcome Disparities among Outborns Needing Therapeutic Hypothermia - Harbert, Mary Jo A.; Sey, Rachelle; Arnell, Kathy; Rasmussen, Maynard (American Journal of Perinatology, 2020)
Objective This study examined patterns of care after birth in newborns treated with therapeutic hypothermia to identify remediable causes for the poorer outcomes observed in outborn infants.Study Design This was a secondary analysis of 150 newborns (68 outborn) prospectively enrolled at our center in the Vermont Oxford Neonatal Encephalopathy Registry from January 2008 to October 2016.Results The 5-minute Apgar's score and cord pH value did not differ, but cord blood gases were obtained far less frequently in outborns (p = 0.002). Outborns needed more chest compressions (p = 0.01) and epinephrine (p = 0.04), and had more brain injury on neuroimaging (p = 0.05). Outborns took longer to reach target hypothermia temperature (p < 0.0001).Conclusion The lack of cord gas values and longer time to reach target temperature observed in the outborns are two observed differences in care that can be potentially remedied by providing education and resources at delivering hospitals in rapid identification of hypothermia candidates, though further research is needed to define the effects of such measures. Possible solutions are also discussed here.
Keywords: humans; newborn; hypothermia; brain injuries; induced hypothermia